Julio Torri, Diálogo de los libros. Edición de Serge I. Zaïtzeff. F.C.E., México, 1980; 282 pp. / Serge I. Zaïtzeff, Julio Torri y la crítica. UNAM, México, 1981; 102 pp. / Serge I. Zaïtzeff, El arte de Julio Torri. Oasis, México; 182 pp. (Alfonso Reyes, 2). - Robb, James Wilis (El Colegio de México, 1985)
Se reseñó el libro: Diálogo de los libros.